HUBUNGAN KEMERDEKAAN BERAGAMA DENGAN PEMBENTUKAN KARAKTER BERBASIS PANCASILA PADA SISWA KELAS X SMA NEGERI COLOMADU TAHUN PELAJARAN 2019/2020 - Rika Puspita Sari; Sugiaryo Sugiaryo; Sutoyo Sutoyo (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2020)
ABSTRACKThe purpouse of this study was to determine whether there is a correlation between religious independence and the character building based on Pancasila at the tenth grade students of SMA Negeri Colomadu in 2019/2020 Academic year. This research was a quantitative research. In this study, the population was 298 students in class X SMA Negeri Colomadu. The sampling technique used was proportional rondom sampling technique. The documentation technique was used to collect data on students at SMA Negeri Colomadu. The questionnaire technique was used to collect data on religious independence and character formation based on Pancasila. The data analysis technique used the productmoment correlation technique. The annalysis results showed thah the value of = 0,742 > r = 0,312 at the 5% significance level. Thus the hypothesis which stated that “There is a positive correlation between religious independence and character formation based on Pancasila at the tenth grade students of SMA Negeri Colomadu in 2019/2020 academic year” was proven true.